Aspectos polêmicos da tutela antecipada prevista no artigo 273, § 6º do código de processo civil - Labud, Aila (2012)
The present essay is about the anticipated guardianship which is referred by the 6 th paragraph of the article 273 from the Code of Civil Procedure. In the beginning we tried to approach the subjects, which somehow are related to this institute commonly called “anticipated guardianship of uncontroversial request”, such as: the judicial acts named sentence and interlocutory decisions; (ii) certain aspects of the anticipated guardianship foreseen in the article 273 from the Code of Civil Procedure, in a general way. From this point on, we went to the effective presentation of the theme, more specifically, about the conceptual question and its juridical nature. With this, it was possible to discourse about the effects, function, and utility of this sort of partial anticipated judgment of litigation or, for some professors, of anticipated guardianship. With this, we tried to delineate all sorts of polemical aspects involved in the subject, like, among others, the suitable resources of the decision that applies the 6th paragraph of the article 273 from the CCP; the revocability of this decision and the way of its fulfillment. The present study concerned itself in approaching the concept of “uncontroversy” for applicability to the legal issue in question, evaluating the necessary requirements for that and considering the current doctrinaire jurisprudential position. Finally, even toward the impossibility of exhausting the matter, what we intended in this work was to discourse about the subject in order to bring the most important aspects, presenting the main doctrinaire discussions and jurisprudential positions that involve the matter